Analysis of factors influencing youth entrepreneurial decisions in Yogyakarta Special Regency - Siahaan, Suci Hidayati Boru (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
This research aims to determine the effect of (1) entrepreneurial knowledge on the entrepreneurial decision; (2) family environment on the entrepreneurial decision; (3) business capital on the entrepreneurial decision; (4) entrepreneurial interest on the entrepreneurial decision; and (5) entrepreneurial knowledge, family environment, business capital, and entrepreneurial interest of youth entrepreneurship decision in Yogyakarta Special Regency. This research method uses SPSS measuring instruments and uses primary data. The data collection data technique uses a questionnaire with a Likert scale of 1-4 and uses regression analysis to analyse data. The result showed that entrepreneurial knowledge, family environment, business capital, and entrepreneurial interest positively and significantly affected entrepreneurial decisions. Based on this result, respondents with entrepreneurial knowledge, family environment support, business capital, and entrepreneurial interest will make entrepreneurial decisions.